1991
DOI: 10.1515/zna-1991-0303
|View full text |Cite
|
Sign up to set email alerts
|

The Microwave Spectrum and Dipole Moment of Hexafluoropropanone

Abstract: We recorded the microwave spectrum of hexafluoropropanone between 7 and 15 GHz using a pulsed molecular beam microwave Fourier transform spectrometer. The rotational constants were determined to be A = 2181.71980(14) MHz, B= 1037.22930(7) MHz, C = 934.89233(8) MHz, the quartic centrifugal distortion constants are D'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Rotational constants were taken from earlier works, ,, and we fitted them to get the internal coordinates (Table ). An isotopic study for the HFA monomer is not known; therefore, we used the calculated parameters for this molecule for further analysis. The 2D-PES scans showed that two types of barriers exist for HFIBE, HFA, and HFAIM (denoted large and small).…”
Section: Resultsmentioning
confidence: 99%
“…Rotational constants were taken from earlier works, ,, and we fitted them to get the internal coordinates (Table ). An isotopic study for the HFA monomer is not known; therefore, we used the calculated parameters for this molecule for further analysis. The 2D-PES scans showed that two types of barriers exist for HFIBE, HFA, and HFAIM (denoted large and small).…”
Section: Resultsmentioning
confidence: 99%
“…In 1990 Grabow et al recorded the rotational spectrum of perfluorinated acetone, that is, hexafluoroacetone (CF 3 ) 2 CO . Hexafluoroacetone is isoelectronic with the target compound of this study, hexafluoroisobutene, with which it also shares an identical CF 3 -C-CF 3 structural motif.…”
Section: Introductionmentioning
confidence: 81%
“…In the 12 000 -14 000 cm On the basis of this review, the data on the infrared spectra of OCS are by far more numerous, more accurate, and concern more states than in the previous global analysis. On the other hand, no new measurements have been performed by Stark spectroscopy, and only one paper has been devoted to the pure rotational spectra (32).…”
Section: The Experimental Datamentioning
confidence: 99%